Why are individuals tracing travel trends? A case study of City Walk in Malaysia - Wang, Zhenbin; Zhang, Hui; Ramachandran, Sridar; Cheng, Suiying (Public Library of Science, 2025)
Studying the emerging travel trends of City Walk is a beneficial activity for young groups. However, there is a lack of research and understanding regarding the motivation and mechanism behind these trends, both in theory and practice. The aim of this study was to investigate the motivation of persons who follow the travel trend of City Walk and evaluate how behavioral intentions are formed by exploring the link between motivation and behavioral intention using the self-determination theory, and social influence theory. Social influence, variety seeking, and self-identification were extrinsic and intrinsic motivations of behavioral intention. A quantitative purposive survey approach was employed, wherein 315 young individuals aged 18 to 40 were recruited to respond. The findings derived from the partial least squares structural equation modeling demonstrate that extrinsic incentives related to social influence, variety seeking, and health care have a considerable impact on behavioral intention, and to some extent influence self-identification. Self-identification has a mediating role in the relationship between health care and behavioral intention. By examining both theoretical and practical aspects, it seeks to provide useful theoretical insights and practical contributions to advance research and industry in the field of rural tourism.